Percutaneous Coronary Intervention in Comorbid Patients with Diabetes Mellitus, Chronic Kidney Disease, and Liver Cirrhosis: Clinical Aspects, Strategy, and Recommendations - F.F. Azizova; M.J. Khalilova; Sh.S. Turaev (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Abstract The combination of diabetes mellitus (DM), chronic kidney disease (CKD), and liver cirrhosis creates a high-risk setting for percutaneous coronary intervention (PCI). This article summarizes current literature and clinical experience, outlining preoperative assessment, interventional strategy, antithrombotic management, measures to reduce contrast-induced nephropathy (CIN), and post-procedural care algorithms. Practical recommendations are provided to support a multidisciplinary approach and decision-making within the Heart Team.